Detection of E. Coli Bacteria in Urinary Tract Infection in Emergency Department at Alimmam Al-Sadiq Hospital: Hilla Iraq - Nidaa f. Azeez, Rawaa M. Mohammed, Ola Abbas Khadhair (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Urinary tract infection (UTIS) is a common microbial infection in community and in all age groups. are alarming worldwide. Therefore, this study aims to detection antibiotics resistance of Escherichia coli (E. coli) bacteria responsible for UTIS Methods: Retrospective chart review for patients admitted to emergency department and diagnosed with UTIS at Al-immam Al-SAdiq Hospital between February to April 2021 was performed. Antimicrobial susceptibility to ampicillin, augmentin (amoxicillin/clavulanate), cefazolin, co-trimoxazole (sulfamethoxazole/trimethoprim), ciprofloxacin, and nitrofurantoin, and cefpodoxime was determined for 101 E. coli urinary isolates. Results: Escherichia coli was the most bacteria causing UTIS representing 93.55, 60.24, and 45.83% of all bacteria isolated from urine culture of pediatric, adult, and elderly, respectively. High rates of resistance to ampicillin (82.76, 58, and 63.64%) and co-trimoxazole (51.72, 42, and 59.09%), among E. coli isolated from pediatric, adult and elderly respectively. Nitrofurantoin was the most active agent, followed by ciprofloxacin, augmentin and cefazolin. 22.77% of E. coli isolates exhibited multiple drug resistance (MDR). Among 66 and 49 isolates resistant to ampicillin and co-trimoxazole, respectively, 34.84 and 42.85% were MDR. In contrast, all isolates resistant to augmentin and nitrofurantoin were MRD, while 72.7 and 82.4% of isolates resistant to ciprofloxacin and cefazolin were MDR. Conclusions: High resistance was observed to ampicillin and co-trimoxazole which commonly used as empirical treatments for UTIS, limiting their clinical use. This necessitates continuous surveillance for resistance pattern of uropathogens against antibiotics.